Analysis on the Significance of the Relationships Between Pay Satisfaction Dimensions and Organizational Citizenship Behavior - Serreqi, Martin (European Journal of Economics and Business Studies, 2020)
The study looks into the relationships of the different dimensions of pay satisfaction with organizational citizenship behaviors (OCBs) directed towards both the individual and the organization. 500 white collar employees of different private sector companies participated in the study. With respect to the influence of the dimensions of pay satisfaction the results showed that there are significant relationships between pay level, pay raises and benefits with citizenship behavior directed at individuals. However, no such relationship exists between structure/administration and citizenship behavior directed at the organization. Limitations and future research directions conclude the study.
Keywords: Significance, Relationships Between Pay Satisfaction Dimensions, Organizational Citizenship Behavior